Utilization of Digitalization on the Quality Of Administrative Services in Karang Wangi Village, Cirebon - Ade Bani Riyan; Muhammad Asril Maulana; Siti Ainul Kholipah; Hanah Wardatul Janah; Endang Ruaesih (Jurnal Indonesia Sosial Teknologi, 2025)
This study examines the impact of digitization on the quality of administrative services in Karangwangi Village, Cirebon, amidst the government’s smart village initiative aimed at improving public service efficiency and village governance. The research aims to analyze community satisfaction, identify challenges in digitalization implementation, and provide strategic recommendations for enhancement. Employing a qualitative case study approach, data were collected through in-depth interviews with village officials and residents, direct observations of digital service usage, and review of relevant documents. Findings reveal that while digitization has positively influenced service speed and transparency, significant obstacles remain, including limited digital literacy among residents, inadequate technological infrastructure, and insufficient training for village officials. Community satisfaction with digital services is generally high, yet access and information transparency need improvement. The study concludes that to maximize the benefits of digital administration, efforts must focus on enhancing infrastructure, expanding training programs for officials and residents, and increasing socialization about digital services. This research offers valuable insights for policy makers and village governments seeking to optimize digital transformation in rural public services and supports broader efforts to modernize administrative functions at the village level.